Non-Invasive and Minimally-Invasive Cerebral Autoregulation Assessment: A Narrative Review of Techniques and Implications for Clinical Research - Sainbhi, Amanjyot Singh; Gomez, Alwyn; Froese, Logan; Slack, Trevor; Batson, Carleen; Stein, Kevin Y.; Cordingley, Dean M.; Alizadeh, Arsalan; Zeiler, Frederick A. (Frontiers in Neurology, 2022)
The process of cerebral vessels regulating constant cerebral blood flow over a wide range of systemic arterial pressures is termed cerebral autoregulation (CA). Static and dynamic autoregulation are two types of CA measurement techniques, with the main difference between these measures relating to the time scale used. Static autoregulation looks at the long-term change in blood pressures, while dynamic autoregulation looks at the immediate change. Techniques that provide regularly updating measures are referred to as continuous, whereas intermittent techniques take a single at point in time. However, a technique being continuous or intermittent is not implied by if the technique measures autoregulation statically or dynamically. This narrative review outlines technical aspects of non-invasive measurement techniques in detail. These non-invasive techniques include neuroimaging methods, transcranial Doppler, and near-infrared spectroscopy. Further, the advantages and limitations are discussed along with how these methods are used to assess CA. At the end, the clinical considerations regarding these various non-invasive techniques are highlighted.